The Cost of Postponement of Bt Rice Commercialization in China - Jin, Yan; Drabik, Dus̆an; Heerink, Nico; Wesseler, Justus (Frontiers in Plant Science, 2019)
We assess the cost of postponement of Bt rice commercialization in China between the years 2009 and 2019 by taking into account the external costs of pesticide use and potential technology spillovers of Bt rice. We estimate the cost of postponement of Bt rice in the analyzed period to be up to 12 billion US dollars per year. Our estimates can contribute to the societal debate on GM crops commercialization in China.